A feasibility study of the usefulness of the TEMPS-A scale in assessing affective temperament in athletes - Białczyk, K; Kłopocki, J; Kryś, J; Jaskulski, M; Lewandowska, A; Szafkowski, R; Ogurkowski, K; Pheby, D; Morten, K; Jaracz, M (MDPI, 2022)
Background and objectives: Current studies show an important role of affective temperament in sport performance. The aim of this study was to assess the feasibility of the use of the TEMPS-A scale, by using it to examine five dimensions of affective temperament in three groups of athletes. We hypothesized that temperament may be a predisposing factor to the level of commitment and type of training. Materials and methods: The study group (N:71, 33 female) consisted of professional canoeists (N:25, aged 18–30), sports pilots (N:21, aged 19–57) and non-professionals regularly performing aerobic exercises (N:25, aged 23–33). The Affective Temperament of Pisa, Paris and San Diego Autoquestionnaire (TEMPS-A) was used to evaluate affective temperament dimensions. Statistical analysis was performed using non-parametric tests. Results: The TEMPS_A scale shows good internal consistency; a hyperthymic temperament was associated with different factors compared to other temperament traits. The most prevalent trait in the study group was hyperthymic temperament. The study group scored higher on hyperthymic and lower on depressive and anxious temperaments when compared with the general population. Canoeists scored higher on cyclothymic temperament compared with non-professional athletes and on cyclothymic and irritable dimensions in comparison with pilots. Pilots obtained significantly lower scores on irritable and anxious temperaments than non-professional athletes. Females scored higher on both hyperthymic and irritable dimensions. No significant differences were found in respect of depressive, cyclothymic and anxious traits. Age was negatively correlated with cyclothymic and irritable temperament scores. Conclusions: TEMPS-A scale is a useful tool for assessing affective temperament in athletes. The results suggest that affective temperament may be a factor influencing physical activity engagement. Different types of activities may be connected with different temperament dimensions. Younger athletes present a higher tendency to mood lability and sensitivity to environmental factors. However, further research is needed, involving larger numbers of subjects.